Respuesta :

Answer: x = 4 and y = -3

Step-by-step explanation:

2x + 4y = -4

2x = -4 - 4y

x = -2 - 2y

Now that we have solved the first equation for x, we plug (-2 - 2y) into the other equation in place of x and then solve for y.

3(-2 -2y) + 5y = -3

-6 - 6y + 5y = -3

-y = 3

y = -3

Now that we know y, we plug it into the original equation and solve for x.

2x + 4(-3) = -4

2x + -12 = -4

2x = 8

x = 4

You can check the answer by plugging both x and y into either of the original equations.